Is HIV Painful? An Epidemiologic Study of the Prevalence and Risk Factors for Pain in HIV-infected Patients. Issue 9 (September 2015) - Lawson, Edwina; Sabin, Caroline; Perry, Nicky; Richardson, Daniel; Gilleece, Yvonne; Churchill, Duncan; Dean, Gillian; Williams, Debbie; Fisher, Martin; Walker-Bone, Karen
Abstract : Objectives: To evaluate the prevalence, impact, and risk factors for pain among a cohort of human immunodeficiency virus (HIV)-infected adults treated with combination antiretroviral therapy if indicated according to current guidelines. Methods: This was a cross-sectional epidemiological observational study. All patients attending 1 HIV-outpatient center in the United Kingdom in a 10-month period were eligible. Patients completed a validated questionnaire enquiring about demographics, HIV factors, and symptoms of pain. Results: Of 1050 eligible participants, 859 (82%) completed a questionnaire. The 1-month period prevalence of pain lasting >1 day was 62.8% among whom 63% reported current pain. The prevalence of pain at most anatomic sites was broadly similar to that observed in population studies using the same questionnaires except that we found considerably higher rates of foot/ankle pain. The median duration of pain was 3 years (range, 0 to 51 y) and the median pain score was 5.0 on an 11-point visual analogue score. Over 40% of people in pain had consulted their primary care physician and >20% were taking analgesics daily. Independent risk factors for current pain were older age ( P =0.001), time since diagnosis of HIV infection ( P =0.001), and receipt of a protease inhibitor-based regimen ( P =0.04). Discussion: Pain, and notably foot/ankle pain, is common among adults living with prevalent HIV and is associated with substantial morbidity and health care utilization.